Evaluation of EUCAST Rapid Antimicrobial Susceptibility Testing for Gram-Negative Bacteria Directly from Positive Blood Cultures - Tian PP; Yang H; Wang T; Wang L; Du MY; Su SS; Zhu LS; Wang XM; Xie LC; Fan W; Tian T; Yi HW (Infection and Drug Resistance)
Peng-Peng Tian,1 Hui Yang,1 Tian Wang,1 Li Wang,1 Meng-Yao Du,1 Shan-Shan Su,1 Li-Sha Zhu,1 Xian-Mo Wang,1 Liang-Cai Xie,1 Wen Fan,1 Tian Tian,2 Hua-Wei Yi1 1Laboratory Department, The First Affiliated Hospital of Yangtze University, Jingzhou, Hubei, People’s Republic of China; 2Ophthalmology Department, The First Affiliated Hospital of Yangtze University, Jingzhou, Hubei, People’s Republic of ChinaCorrespondence: Hua-Wei Yi, The First Affiliated Hospital of Yangtze University, No. 55 Jianghan North Road, Shashi District, Jingzhou, Hubei, 434000, People’s Republic of China, Email yihuawei0902@126.com Tian Tian, Email dmtt-316@163.comPurpose: This study aims to evaluate the accuracy of EUCAST rapid antimicrobial susceptibility testing (RAST) for Gram-negative bacteria directly from positive blood cultures, comparing it with short-term incubation (5– 7 hours) and conventional broth microdilution methods.Methods: A total of 139 Gram-negative isolates were tested. RAST results were assessed at 4 h, 6 h against minimal inhibitory concentration results using the short-term incubation (5– 7 h) method, while at 16– 20 h, the RAST results were compared to conventional method. For those with interpretable results, CLSI M52 was used to define cutoffs for equivalence in antimicrobial susceptibility testing.Results: Among all isolates, 80.6% (112/139) were successfully interpreted based on EUCAST RAST breakpoints, including Escherichia coli (81), Klebsiella pneumoniae complex (17), Pseudomonas aeruginosa (10) and Acinetobacter baumannii (4). The overall category agreements for all tested antibiotics were 98.9%, 99.5%, and 99.7% at 4, 6, and 16– 20 hours, respectively, for E. coli, and 100% for K. pneumoniae, P. aeruginosa, and A. baumannii. The area of technical uncertainty rate significantly decreased over time, from 9.1% at 4 hours to 3.1% at 16– 20 hours (p < 0.05). The method effectively identified extended-spectrum beta-lactamase (ESBL)-producing and carbapenem-resistant bacteria, demonstrating performance comparable to the BD system. Additionally, results for other Enterobacterales could be interpreted using the RAST breakpoints for E. coli. The integration of RAST into routine workflows provides rapid and accurate results without incurring additional costs or labor.Conclusion: RAST is a reliable and cost-effective method for testing Gram-negative bacteria directly from blood cultures, significantly reducing turnaround time. Utilizing RAST at various reading times (6 hours and 16– 20 hours) optimizes clinical workflows, enhances antimicrobial stewardship, and improves patient outcomes.Keywords: blood culture, rapid antimicrobial susceptibility testing, EUCAST, gram-negative bacteria, bloodstream infection, short-term incubation